The Philosophical Forum. Published with the cooperation of the Departament of Philosophy of Baruch College of the City University of New York, v. XX, n. 1-2, Fall-Winter 1988-89 - Jalif de Bertranou, Clara Alicia (1990)
Fil: Jalif de Bertranou, Clara Alicia.